Application of the Tonnis Game Branch of Sports in Improving Physical Fitness - Ragil Setiawan; Hartati; Herri Yusfi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research investigates the impact and correlation of tennis games on the physical fitness of students at State Elementary School 11 Tanjung Batu. The study employs a quantitative descriptive approach to analyze data collected in percentage form, which is then discussed descriptively using a solid theoretical framework. The research involved 40 students from Tanjung Batu State Elementary School during the academic year 2023-2024. The findings reveal a robust relationship between the application of tennis games and improvements in physical fitness among students. The correlation coefficient (r) of 0.774 indicates a strong relationship, highlighting the effectiveness of tennis games in enhancing physical fitness levels. This is particularly evident in fostering creativity and skill development in small ball sports within the physical education curriculum. The implications drawn from this research underscore the practical benefits of incorporating tennis games into educational settings to bolster students’ physical fitness. The successful implementation of tennis games as a means to enhance physical fitness outcomes underscores its viability and relevance in educational practices. This research contributes valuable insights into the positive outcomes of integrating sports like tennis into physical education programs, emphasizing its role in promoting overall health and skill development among school children. In conclusion, the study substantiates the significance of tennis games not only as a recreational activity but also as a structured approach to improving physical fitness and fostering motor skill development among elementary school students. The findings encourage further exploration and adoption of tennis and similar activities within educational curricula to optimize physical education outcomes.